5. Methodological Aspects Regarding the Integrity of the Musical-Didactic Activities During the Musical Education Lesson - Caliga Marina (Sciendo, 2022)
The purpose of the musical art is to give complete knowledge about the world and about oneself. Musical education aims to form the artistic culture of the student, as a component of the spiritual culture. Due to the following fields of activity such as reception of works of art, vocal/choral/instrumental interpretation, creation, and artistic reflection, this type of education is treated as a continuous individual process of personality formation through multiple musical-didactic communication activities with musical art.